Vernuwing in Historiese Jesus-Navorsing - Craffert, Pieter F. (Verbum et ecclesia, 2001)
The approaches of the Jesus Seminar and the Third Quest to the study of the historical Jesus are compared. Three different aspects are considered: Why is it done?; What is it about? and How is it done? Despite differences, it is shown that on a philosophical and world-view level, they share a similar positivistic historiography and modernist worldview. The main distinction is that theTthird Questers supplement the latter with a supernatural element. Further, it is argued that progress in historical Jesus research cannot be achieved by providing new answers to old questions or by means of mere adjustments to any of these approaches. What is needed is an approach that asks different questions and goes in totally new directions. The outlines of such an approach is sketched.